Strategi Bank Syariah Dalam Pembiayaan Mikro pada Masa Pandemi Covid-19 - Annisa Yasrien Algaisya; Abrista Devi; Sofian Muhlisin (LPPM IAI Nasional Laa Roiba Bogor, 2022)
At the end of 2019 there was a global change due to the corona virus disease which was then called Covid-19 which first appeared in Wuhan, China. WHO officially announced this respiratory virus as a pandemic in March 2020. Covid-19 has caused the death rate to continue to increase both in the world and in Indonesia. Covid-19 affects various sectors, one of the sectors most affected is the economic sector. It is known that during the Covid-19 pandemic, Indonesia's GDP decreased, the unemployment rate increased, and also in the microeconomic sector many MSMEs experienced a decline in business and even bankruptcy. Whereas MSMEs are one of the most influential sectors for GDP in Indonesia. MSME turnover has decreased while MSMEs need capital assistance for their business. To overcome and support MSMEs, the role of financial institutions is very much needed. One of the Financial Institutions that plays a role in providing capital for MSMEs is Islamic Banking, this is because Islamic Banking focuses on the real sector, even though on the Islamic Banking side there needs to be a strategy before providing financing so that Islamic Banking can maintain financial stability during this pandemic. Therefore, this research is entitled: Strategy of Islamic Banks in Microfinance during the Covid-19 Pandemic (Case Study of BSI KCP Sentul). With the formulation of the problem; (1) Problems encountered in microfinance at BSI KCP Sentul during the pandemic; (2) Solutions to problems encountered in microfinance at BSI KCP Sentul during the pandemic; (3) Strategy of BSI KCP Sentul in microfinance during the pandemic. The method used is descriptive qualitative by interviewing 3 people from BSI KCP Sentul. This study uses primary data, namely interviews. The results of this study are: (1) the problems faced are in the form of internal problems which include performance such as weak financing analysis, limited human resources in the field of financing settlement, weaknesses in bank policies that apply high product prices, and also access to Islamic banking which is still difficult to reach. Meanwhile, the external problems faced in the form of problems stemming from the character of customers, covid-19, government regulations, and the legality of MSMEs; (2) The solution from the internal banking side is to carry out managerial supervision of the Bank and conduct regular communication to customers, improve the capacity of human resources in terms of micro-financing, and provide indirect financing through BPRS; (3) The first banking strategy is to provide financing to MSMEs that are not significantly affected by Covid-19, establish a microfinance service center, and provide lower margins. Keywords: Covid-19, MSMEs, Islamic Banking.